PENGENALAN FASILITAS OPERASI PERKERETAAPIAN GUNA MENINGKATKAN PENGETAHUAN SISWA SMK DI BIDANG PERKERETAAPIAN - Puspitasari, Mariana Diah; Oktaria, Dhina Setyo; Winjaya, Fathurrozi; Iswanto, Ary Putra; Damayanti, Ajeng Tyas (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
The importance of railway knowledge in the growing world of work, as well as the need to address the lack of understanding encountered among vocational students. The change from supply-oriented to demand-oriented curriculum is the main focus in improving vocational education. The Introduction of Railway Operation Facilities to Increase the Knowledge of Vocational Students in the Railway Field aims not only as a means of approach and promotion to the community about the existence of the Indonesian Railway Polytechnic Madiun campus, but also as a medium to escalate students' skills and knowledge in the field of railway operation facilities. This activity explains the legal basis related to railway operating facilities, including legal products that regulate operational aspects, safety, and optimization of all resources in the railway industry. In addition, it also explains about railroad operating facilities and their functions.